The re-signification of education in Hannah Arendt - Oliveira, Cícero Josinaldo da Silva (Argumentos - Revista de Filosofia, 2025)
The Arendtian redefinition of education as a response to and preparation for the fact that humans are born into the symbolic and material legacy constituting the human world implies an integration with the author's philosophical thought, even as it serves as a critical intervention in the debate surrounding the progressive pedagogical programs then influential in the American educational system. In this text, we revisit this critical debate in light of some of the thematic and conceptual connections within Arendt's thought, particularly regarding the category of "the human condition," given its decisive role in the context of the undertaken redefinition.